Genetic Comparison of ESBL-Producing Escherichia coli from Workers and Pigs at Vietnamese Pig Farms - Duong Thi Quy Truong; Yaovi Mahuton Gildas Hounmanou; Son Thi Thanh Dang; John Elmerdahl Olsen; Giang Thi Huong Truong; Nhat Thi Tran; Flemming Scheutz; Anders Dalsgaard (MDPI AG, 2021)
We analyzed and compared genomes of Extended Spectrum Beta-Lactamase (ESBL)-producing Escherichia coli from pigs and pig farm workers at 116 farms in Vietnam. Analyses revealed the presence of blaCTX-M-55, blaCTX-M-27, blaCTX-M-15, blaCTX-M-14, blaCTX-M-3, blaCTX-M-65, blaCTX-M-24, blaDHA-1, and blaCMY2 in both hosts. Most strains from pigs contained quinolones (qnr) and colistin resistance genes (mcr-1 and mcr-3). Isolates predominantly harbored more than one plasmid replicon and some harbored plasmid replicons on the same contigs as the ESBL genes. Five strains from farm workers of ST38 (2), ST69 (1), and ST1722 (2) were classified as either uropathogenic E. coli (UPECHM)/extraintestinal pathogenic E. coli (ExPECJJ) or UPECHM, and the remaining were genetically distinct commensals. A high heterogeneity was found among the ESBL-producing E. coli from pigs and workers, with most isolates belonging to unrelated phylogroups, serogroups, and sequence types with >4046 Single-Nucleotide Polymorphisms-(SNPs). In comparing the genomes of pig isolates to those from humans, it appeared that ESBL-producing E. coli in workers did not predominantly originate from pigs but were rather host-specific. Nevertheless, the occurrence of ESBL-producing E. coli carrying plasmid-mediated colistin and quinolone resistance genes in pigs could represent a potential source for horizontal transmission to humans through food rather than direct contact.